1998
DOI: 10.1164/ajrccm.157.6.9705028
|View full text |Cite
|
Sign up to set email alerts
|

Early Inhibition of Mycobacterial Growth by Human Alveolar Macrophages is not Due to Nitric Oxide

Abstract: Phagocytic cells provide the first line of defense against mycobacteria. We examined the relative mycobacteriostatic contributions of normal human alveolar macrophages (HAM), peripheral blood monocytes (PBM), and polymorphonuclear leukocytes (PMN) in the early time period after infection with mycobacteria (48 h). Cells were infected with Mycobacterium bovis (BCG) or M. tuberculosis H37Ra and their ability to inhibit growth was determined by mycobacterial incorporation of [3H]uracil. HAM inhibited the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 25 publications
7
54
0
Order By: Relevance
“…Similarly, the bactericiostatic activity of macrophages cultured at high density could not be attributed to the preferential generation of NO by these cells, because treatment with the inducible NO synthase inhibitor L-NIL did not influence their ability to control mycobacterial replication. Consistent with these observations, prior studies have shown that although human macrophages express inducible NO synthase after mycobacterial infection (35,36), the levels of NO produced are low, and the inhibition of NO production by human macrophages does not reproducibly increase mycobacterial growth (36,37). Increased apoptosis of macrophages infected with mycobacteria has been described and in some but not all cases has been associated with mycobacterial killing (38 -41).…”
Section: Figuresupporting
confidence: 52%
“…Similarly, the bactericiostatic activity of macrophages cultured at high density could not be attributed to the preferential generation of NO by these cells, because treatment with the inducible NO synthase inhibitor L-NIL did not influence their ability to control mycobacterial replication. Consistent with these observations, prior studies have shown that although human macrophages express inducible NO synthase after mycobacterial infection (35,36), the levels of NO produced are low, and the inhibition of NO production by human macrophages does not reproducibly increase mycobacterial growth (36,37). Increased apoptosis of macrophages infected with mycobacteria has been described and in some but not all cases has been associated with mycobacterial killing (38 -41).…”
Section: Figuresupporting
confidence: 52%
“…In addition, it has been shown that AM in lung sections from patients with IPF [9], chronic obstructive pulmonary disease (COPD) [23] and sarcoidosis [2] display strong immunoreactivity for NOS2 protein in situ. However, many attempts to induce NOS2 mRNA expression and/or NO production by human AM in vitro failed [7,24,25]. As shown in the present investigation, AM isolated from lung tissue samples exhibited immunoreactive NOS2 protein ex vivo and its level was preserved or slightly decreased during 18-h culture periods with or without stimuli such as pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 47%
“…Although several investigators have shown that human AM can be induced to express NOS2 in vivo, their ability to express NOS2 and to generate NO in response to an in vitro stimulation is still under debate [6,7]. One reason for this controversy may arise from complex inflammatory processes within the alveoli responsible for NOS2 messenger ribonucleic acid (mRNA) expression, enzyme production, and NO generation by human AM.…”
mentioning
confidence: 99%
“…Although several reports concerning NOS2 expression in normal human lung tissue have provided evidence that peripheral lung parenchyma, as well as resident lung macrophages, do not express NOS2 mRNA (10) and that no specific immunostaining for NOS2 protein can be observed in alveolar compartments (18), the accumulation of NOS2 protein and NO production have been documented in AM isolated from patients with active pulmonary tuberculosis (22) and acute respiratory distress syndrome (17). However, many attempts to induce NOS2 mRNA expression and/or NO production by human AM in vitro failed (5,7,10). In contrast to data from Guo et al (10) and Kobzik et al (18), but in accordance with our findings, Saleh et al (31) demonstrated a weak expression of nitrotyrosine and NOS2 in the airway epithelium and AM and abundant expression of NOS3 in the pulmonary endothelium and airway epithelium of normal parts of human lungs obtained by pneumectomy performed because of lung cancer.…”
Section: Discussionmentioning
confidence: 99%